The Use of Figurative Language in the Poems by John Ashbery - Sri Wahyuna; Arifin Syamaun; Chairina Chairina (Universitas Syiah Kuala, 2020)
Figurative language was a part of the literary work which created from philosophical thought or the effect of poets’ feeling which played some words and used as an interesting and creative comprehension. This study discussed about the use of figurative languages in the poems by John Ashbery based on the theory of Bain, Baety, and Hunter (1973) and describing the contextual meaning of the figurative language. The design of this study was descriptive qualitative research in nature. The results of the study showed that some types of figurative language used in the poems by John Ashbery such as metonymy, metaphor, hyperbole, alliteration, etc. The writer collected the data through three poems by John Ashbery which were gathered from the poetry books by John Ashbery; A Wave Poem (1984), The Tennis Court Oath (2011), and Self-Portrait in a Convex Mirror (2007). The use of figurative language is suggested to use in improving student’s critical thinking and creativeness.